Tanggap Pertumbuhan dan Hasil Tanaman Sawi Pagoda (Brassica norinosa) Terhadap Berbagai Dosis Pupuk AB MIX Metode Hidroponik dengan Sistem Rakit Apung - Inka Dahlianah; Arwinsyah Arwinsyah; Pebriana Kartika Sari; Suhal Nur Rahma (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2020)
The purpose of this research to find a suitable dose of ab mix for pagoda mustard plant, has been carried out on Jalan Sukakarya, Sukarami, Palembang. The trial was conducted in October to December 2019 who have used a perfectly randomized design method is a single factor group with 5 treatments and 4 replications. Each treatment consisted of 3 plant so there was 20 and a total of 60 plants. This was the dose of AB mix fertilizer (D), namely D1 = 850 ppm, D2 = 1050 ppm, D3 = 1250 ppm, D4 = 1450 ppm, and D5 = 1650 ppm. The observed parameters were plant height, root length, and wet basis, measured at the end of the study. The results showed that the highest yield of D3 treatment was obtained at root length and plant wet basis respectively of 15.77 cm and 149.97 g and the highest yield of D4 treatment was obtained on plant height parameters of 12.91 cm, and the lowest yield was very significant in D5 respectively 9.24 cm, 9.57 cm and 112.50 cm